Target detection and recognition algorithm for moving UAV based on machine vision - Jun, Mao (Cluster computing, 2019)
To solve the shortcomings that current robot vision system accuracy is instable, unit operation time is overlong and automatic compensation function is lacked, this paper proposes robot vision system based on trinocular vision from the perspective of system hardware structure improvement and software algorithm optimization. Firstly, logic communication channel among PLC sensor, robot and vision PC shall be established, to realize real-time acquisition and processing of operation condition of material. Then design nine-point calibration method according to scaling, rotating and translation parameters between robot and vision coordinate system, and calibrate three industrial cameras to realize accurate binding of image pixel coordinate and robot world coordinate. Finally, choose region-of-interest, optimize the minimum mean square error matching algorithm and realize balance of system accuracy and speed according to project standard of product. Experimental test result shows that compared with current robot vision system, system in this paper has higher vision accuracy and operation efficiency.